Alcohol Induced Brain and Liver Damage: Advantages of a Porcine Alcohol Use Disorder Model - Shin, Soo K.; Kaiser, Erin E.; West, Franklin D. (Frontiers in Physiology, 2021)
Alcohol is one of the most commonly abused intoxicants with 1 in 6 adults at risk for alcohol use disorder (AUD) in the United States. As such, animal models have been extensively investigated with rodent AUD models being the most widely studied. However, inherent anatomical and physiological differences between rodents and humans pose a number of limitations in studying the complex nature of human AUD. For example, rodents differ from humans in that rodents metabolize alcohol rapidly and do not innately demonstrate voluntary alcohol consumption. Comparatively, pigs exhibit similar patterns observed in human AUD including voluntary alcohol consumption and intoxication behaviors, which are instrumental in establishing a more representative AUD model that could in turn delineate the risk factors involved in the development of this disorder. Pigs and humans also share anatomical similarities in the two major target organs of alcohol- the brain and liver. Pigs possess gyrencephalic brains with comparable cerebral white matter volumes to humans, thus enabling more representative evaluations of susceptibility and neural tissue damage in response to AUD. Furthermore, similarities in the liver result in a comparable rate of alcohol elimination as humans, thus enabling a more accurate extrapolation of dosage and intoxication level to humans. A porcine model of AUD possesses great translational potential that can significantly advance our current understanding of the complex development and continuance of AUD in humans.